Analisis Kelayakan Isi Materi pada Buku Teks Sahabatku Indonesia BIPA 5 (International Forum of Researchers and Lecturers, 2026)
The provision of high-quality instructional materials is a crucial factor in the success of Indonesian Language for Foreign Learners (BIPA) programs, particularly at the advanced level which requires highly contextual content. This study aims to describe and evaluate the content suitability of the Sahabatku Indonesia BIPA 5 textbook. A descriptive-qualitative method was employed, with data collected through document studies. Purposive sampling was used for data analysis, and data validity was ensured through triangulation. The analysis focused on three primary dimensions: (1) the alignment of material descriptions with communicative objectives, (2) the accuracy of the instructional content, and (3) the quality of learning support materials. The findings indicate that the Sahabatku Indonesia BIPA 5 textbook achieves a suitability percentage of 87.5%, categorizing it as highly feasible for instructional use. The implications of this research are expected to serve as a reference for BIPA practitioners in selecting standardized teaching materials and provide constructive feedback for textbook developers in refining competency-based communicative materials.